CON: Should patients with nonalcoholic steatohepatitis fibrosis undergo bariatric surgery as a primary treatment?. Issue 1 (22nd July 2022) - Newton, Eric B.; Pan, Jason; Chung, Waihong
Abstract : Content available: Author Interview and Audio Recording